Pengembangan Desa Adat Gelgel sebagai Wisata Spiritual - I Made Mardika; Agus Kurniawan; Ni Komang Arini Satyawati; A. A. Ayu Dewi Larantika (Postgraduated Community Service Journal, 2022)
Community Service on the development of the Gelgel Traditional Village as Spiritual Tourism aims to empower the community in realizing the Gelgel Traditional Village as a Spiritual Tourism Destination Area. The service partner is the Bendesa Adat Gelgel with the target audience of the Gelgel Traditional Village ‘krama’ community groups. The selection of Gelgel Traditional Village as the location of service because Gelgel has the potential to be developed into a spiritual tourism model, in accordance with the development direction of the Klungkung Regency government, and has become a guided village for the Postgraduate Program of Warmadewa University. This second year of service is programmed on the arrangement of temples and packaging of spiritual DTW icon designs as well as the preparation of Human Resources for spiritual tourism managers. The three focus partner problems that were solved were: (1) there was no physical form of "icon" information (nameplate, candi bentar building) to mark the Gelgel Traditional Village as the center of the Swecapura palace and the kawitan center complex for various clans/soroh in Bali, (2) the arrangement of the potential of cultural heritage that can be packaged into a Spiritual tourism attraction has not been carried out, (3) the human resources of Pekraman Village are not yet skilled in utilizing and managing the potential of Spiritual Tourism they have. The solutions offered are: (1) Assistance in drafting the 'icon' design for the Royal Swecarapura Center and Kawitan centers throughout Bali to support Gelgel Village as a Spiritual DTW, (2) FGD in structuring and packaging Spiritual Tourism, (3) Assistance in heritage management temple culture by Gelgel Traditional Village as a collaborative Spiritual Tourism. The outputs produced are articles in national journals with ISSN, activity videos, publications in print/online media, increased competitiveness, increased application of science and technology, and improved values in society. Additional benefits are in the form of IPR posters that are registered as copyrights.